Straight to the back: Femoral triple lumen catheter misplaced in a lumbar vein - George Horani, MD; Ahmad Qatanani, DO; Mubarak Yusuf, MD; Mourad Ismail, MD (Radiology Case Reports)
Central venous catheters are devices inserted into large central veins, usually internal jugular, femoral, or subclavian and serve multiple purposes including administration of vasoactive medications, dialysis, plasmapheresis, total parenteral nutrition, among others. It is considered a relatively safe procedure when performed by experienced clinicians, especially under ultrasound guidance. However, complications are not uncommon and include arterial puncture, injury to nearby structures such as lung puncture leading to pneumothorax, bleeding, infection, and line misplacement. We present a case of a triple lumen catheter which was misplaced in a small lumbar vein side-branch while attempting a left groin approach. This finding was discovered on CT scan of the abdomen and pelvis, after which the catheter was repositioned with proper placement.